Abnormal Cerebral Blood Flow in Childhood Autism - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Brain-perfusion single photon emission computed tomography was used to determine regional cerebral blood flow (rCBF) in 23 children with infantile autism and 26 non-autistic controls, evaluated at the National Center of Neurology and Psychiatry, Kodaira City, Tokyo, Japan.